Position specific peak impact and running demands of professional rugby union players during game play - Peek, R. J.; Middleton, K. J.; Gastin, P. B.; Carey, D. L.; Clarke, A. C. (International Journal of Sports Science & Coaching, 2021)
This study quantifies the maximum number of impacts and peak running demands during 1- to 10- minute rolling window periods in elite rugby union matches using a multi-team dataset (n = 2232 player-games). Maximum values for impacts (impacts·min-1) and running (m·min-1) were calculated for 161 athletes from four teams across the 2018 and 2019 Super Rugby seasons. The effect of window duration and playing position on peak impact and running demands were estimated using linear mixed effect models and prediction intervals. The peak impact and running demands for a 1-min period were 4.5 - 5.5 impacts·min-1 and 150 - 180 m·min-1, depending on playing position. While small variations in mean impact and running movements could be observed by position, the large prediction interval and individual player variation meant that there was no practically meaningful difference by position. As such, when prescribing training drills to replicate the peak demands in rugby union, impact and running movements of players can be similar, regardless of position. Using a prediction interval allows us to identify the range where the demands in a future game may fall, and are beneficial to use when also trying to prepare players for the demands of rugby union.